Observation of piezoelectric response on tungsten doped barium zirconium titanate ceramics - Moura, Francisco; Simões, Alexandre Zirpoli; Zaghete, Maria Aparecida [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Scientific Publishers, 2010)
This study describes observation of piezoelectric response of Ba(Zr 0.10Ti 0.90.O3 ceramics modified with tungsten (BZT:2W) by the mixed oxide method. According to X ray diffraction analysis, the ceramics are free of secondary phases. Transmission electron microscopy (TEM) analyses reveals the absence of segregates in the grain boundaries indicates the high solubility of WO3 in the BZT matrix. The dielectric permittivity measured at a frequency of 10 KHz was equal to 6500 with dieletric loss of 0.15. A typical hysteresis loop was observed at room temperature. Electron Paramagnetic Resonance (EPR) analyses reveals that substitution of W6+ by Ti4+ causes distortion in the crystal structure changing lattice parameter. Polarization reversal was investigated by applying dc voltage through a conductive tip during the area scanning. Piezoelectric force microscopy images reveals that in-plane response may not change its sign upon polarization switching, while the out-of-plane response does. Copyright © 2010 American Scientific Publishers.
Keywords: Ceramics; Dieletric Response; Mixed Oxide; Piezoelectricity; DC voltage; Dielectric permittivities; Dieletric loss; High solubility; Mixed oxide; Mixed oxide method; Out-of-plane; Piezoelectric force microscopy; Piezoelectric response; Polarization reversals; Polarization switching; Room temperature; Secondary phasis; Transmission electron microscopy tem; Typical hysteresis loop; Zirconium titanate; Barium; Crystal structure; Crystallography; Grain boundaries; Magnetic resonance; Paramagnetism; Permittivity; Transmission electron microscopy; Tungsten; X ray diffraction analysis; Zirconium; Ceramic materials